Damage processes in extended laser exposures using an in vitro model - Pope, Nathaniel J.; Ha, Jin; Melzer, Madeline E.; Lopez, Priscilla; Tijerina, Amanda; Noojin, Gary D.; Denton, Michael L. (Frontiers in Ophthalmology, 2025)
Retinal pigment epithelial (RPE) cells are sensitive to both photothermal and photochemical damage when exposed to lasers with wavelengths associated with the retinal blue light hazard. Laser power density (irradiance) and exposure duration primarily dictate the damage mechanism. Relatively high irradiances and short exposure durations typically lead to melanin-dependent photothermal damage, whereas low irradiance and long duration exposures are required for photochemical pathways. However, little is known about damage mechanisms at intermediate irradiances and durations for pigmented cells. The current Z136.1–2022 laser safety standard from the American National Standards Institute (ANSI) does not consider combined photothermal and photochemical damage processes. In addition, the ANSI Z136.1 standard classifies photochemical damage as nonthermal. Here, we use extended laser exposure parameters in an in vitro RPE cell model (ATCC CRL-4000) to show that elevated temperatures accelerate photochemical damage mechanisms. In addition, for 447-nm exposure conditions leading to damage considered neither purely photothermal nor photochemical, there is a reduced requirement for the thermal component for cell death. Our results suggest the need to address safety for lasers with blue wavelength emission, as in ophthalmic devices.